2016
DOI: 10.1016/j.conbuildmat.2016.10.058
|View full text |Cite
|
Sign up to set email alerts
|

A database on flexural and shear strength of reinforced recycled aggregate concrete beams and comparison to Eurocode 2 predictions

Abstract: A comprehensive database of recycled aggregate concrete and companion natural aggregate concrete beams' flexural and shear strength was compiled from 217 experimental results. Strict criteria were applied to determine the failure type. Sub-databases were formed with beams failing in flexure and shear with and without stirrups. On each subdatabase the applicability of Eurocode 2 provisions for flexural and shear strength to recycled aggregate concrete beams was tested. The results show that flexural and shear s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 35 publications
(69 reference statements)
0
20
0
Order By: Relevance
“…Based on the literatures reported [37], more researches on shear performance of reinforced recycled aggregate concrete beams without web reinforcement have been carried out and evaluated with the current design codes. Comparatively, less studies were performed on the shear behavior of reinforced recycled aggregate concrete beams with stirrups, thus further researches and experimental results are necessary.…”
Section: Research Significancementioning
confidence: 99%
“…Based on the literatures reported [37], more researches on shear performance of reinforced recycled aggregate concrete beams without web reinforcement have been carried out and evaluated with the current design codes. Comparatively, less studies were performed on the shear behavior of reinforced recycled aggregate concrete beams with stirrups, thus further researches and experimental results are necessary.…”
Section: Research Significancementioning
confidence: 99%
“…It is noteworthy that two thorough review studies by Silva et al [40] and Tošic et al [41] have clearly shown that the design code Eurocode 2 can provide a good prediction for the load-carrying capacity of RRC beams without stirrups. However, for the beams with stirrups, which are more significant in practice-the predictions by Eurocode 2 showed a remarkable gap compared to the measurements, suggesting that the underlying mechanisms still needed to be revealed towards more reliable designs.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in such cases (with shear reinforcement), the detrimental effects are not as prominent as in beams without shear reinforcement. Tošić et al [ 39 ] added their own test data to a comprehensive database for RAC beams, and evaluated the beams’ flexural and shear strengths using European design code. In the shear loading case, the code can successfully predict the ultimate force of RAC beams without stirrups, but it fails for the beams with stirrups.…”
Section: Introductionmentioning
confidence: 99%